UCI sports nutrition project: Race nutrition for road cycling - Jeukendrup, A. E.; Redegeld, M.; Martins, G.; Whitfield, J.; Burke, L. M.; Mujika, I.; Dolan, E.; Gonzalez, J. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2026)
This review outlines recent advances in race nutrition support for professional road cycling, emphasizing individualized, context-specific strategies over generic recommendations. Within the past couple of decades, there have been several changes in nutritional demands and practices within road cycling including (1) a change in the distribution of intensity across a stage or 1-day race; (2) an increase in "on-bike" carbohydrate intake coinciding with integrated "training the gut" practices; and (3) better maintenance of neutral energy balance across stage races. Specifically, race tactics now, generally demand a higher intensity earlier within a stage (or 1-day race), thereby also increasing energy and carbohydrate requirements and utilization early on within a stage. Concomitantly, there has been an increase in reported intake of carbohydrates "on-bike," from *30 to 60 g/hr pre-2010, to 90 and even 120 g/hr and higher in the present day. There is also evidence that the maintenance of energy balance across stage races has improved over this timeframe. These topics are discussed in detail alongside additional nutritional challenges and strategies relevant to professional road cycling, such as daily energy, fluid, and macronutrient distribution, which are often tailored to rider characteristics (e.g., body size, role, performance goals) and race-specific factors (e.g., course profile, environmental conditions).